Current and experimental drug therapy for the treatment of polycystic ovarian syndrome. (2nd August 2020) - Della Corte, Luigi; Foreste, Virginia; Barra, Fabio; Gustavino, Claudio; Alessandri, Franco; Centurioni, Maria Grazia; Ferrero, Simone; Bifulco, Giuseppe; Giampaolino, Pierluigi
ABSTRACT: Introduction: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects 8–13% of reproductive-age women. Irregular periods, hirsutism, or infertility are the most common clinical presentations of patients affected by PCOS. This syndrome is also linked to metabolic abnormalities such as type 2 diabetes, insulin resistance and obesity. The optimal therapeutic approach is still unknown. Areas covered: This narrative review offers an overview of the literature on current and experimental pharmacological options for treating PCOS and highlights ongoing clinical trials. Several electronic databases were searched and current research registers were analyzed to the present year. The papers selected for this review were critically analyzed, and all data available were summarized, organized, and explored to derive key information. Expert opinion: The main goal of PCOS treatment is to obtain a metabolic and hormonal balance. Optimal PCOS therapy should be direct to the reproductive abnormalities and the entire spectrum of endocrine and metabolic complications that appear to have a long-term negative impact on PCOS patient health, as in post-menopausal period. The discovery of new mechanisms in PCOS pathogenesis will offer the possibility of testing new drug classes.